2021
DOI: 10.7150/ijms.53655
|View full text |Cite
|
Sign up to set email alerts
|

Timing of mTORI usage and outcomes in kidney transplant recipients

Abstract: The introduction of mammalian target of rapamycin inhibitors (mTORi) as immunosuppressive agents has changed the landscape of calcineurin inhibitor-based immunosuppressive regimens. However, the timing of mTORi conversion and its associated outcomes in kidney transplantation have conflicting results. This study investigated the effect of early or late mTORi post-transplant initiation on major transplant outcomes, including post-transplant malignancy, in kidney transplant recipients in our center. We enrolled 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…First, this was a retrospective study with a limited sample size. Second, due to limitations in sample collection, all the patients in our study groups were female; nonetheless, this is consistent with the finding that most UCKT individuals in the Taiwanese population are female [ 11 , 82 ]. Additional studies with larger sample sizes are required to achieve conclusive results.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…First, this was a retrospective study with a limited sample size. Second, due to limitations in sample collection, all the patients in our study groups were female; nonetheless, this is consistent with the finding that most UCKT individuals in the Taiwanese population are female [ 11 , 82 ]. Additional studies with larger sample sizes are required to achieve conclusive results.…”
Section: Discussionsupporting
confidence: 85%
“…The standardized incidence ratio of urinary tract malignancies (among which bladder cancer was the most common) among recipients of a kidney transplant was 10.93 (95% CI, 9.20–12.99) [ 10 ]. Furthermore, in our previous single-center retrospective study, the most common PTMs were UC and hepatocellular carcinoma [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, this was a retrospective study with a limited sample size. Second, due to limitations in sample collection, all the patients in our study groups were female; nonetheless, this is consistent with the finding that most UCKT individuals in the Taiwanese population are female [11,60]. Additional studies with larger sample sizes are required to achieve conclusive results.…”
Section: Discussionsupporting
confidence: 83%
“…10 Department of Pathology, Kaohsiung Medical University Hospital, Kaohsiung Medical University, Kaohsiung, Taiwan. 11 Department of Medical Research, Kaohsiung Medical University Hospital, Kaohsiung, Taiwan. 12 Ph.D.…”
Section: Abbreviationsmentioning
confidence: 99%
“…3,29 Our previous study demonstrated that UC was most common renal pelvic or bladder malignancy observed following kidney transplants in Taiwan. 30 Increasing evidence from genomic studies has gradually revealed the molecular landscape of UTUC and identifying numerous gene alterations that are promising targets for gene therapies.…”
Section: Ntrk3 Expression Associated With Cellular Migration and Inva...mentioning
confidence: 99%